Efficient nonlinear modeling of strong wood frame shear walls for mid-rise buildings. (15th July 2020) - Estrella, Xavier; Guindos, Pablo; Almazán, José Luis; Malek, Sardar
Highlights: A new nonlinear modeling approach for 'strong' wood frame walls is proposed. The anchorage system has a significant contribution to the interstory drift. The nailing properties have a significant effect on the anchoring system demands. The nailing pattern can be optimized to increase the capacity of the wall. Abstract: Designing mid-rise timber buildings in seismic areas requires stronger wood frame shear walls compared to those required in low-rise structures. Despite some experimental research has been conducted lately to demonstrate the difference between the lateral response of such 'strong' walls and conventional ones, investigations on numerical models that could reproduce their nonlinear behavior under seismic loads are limited. This paper presents an efficient nonlinear modeling approach to better understand such behavior under large displacement demands. The numerical model was validated using a set of twelve real-scale experiments. The model predictions showed an accuracy of ±8% for 1:1 walls and proved its suitability to capture the post-peak phenomena such as force degradation, stiffness degradation, and pinching. For the aspect ratios investigated, anchorage system demands were found to remain 50% below the failure capacity. It was also shown that redesigning the nailing pattern can increase the capacity of strong wood frame walls by up to 10%. Finally, the application of the developed numerical model in calibrating simpler single-degree-of-freedom (SDOF) models for reproducing the hysteretic response of strong walls was discussed. Since shear behavior governs the deformation of wood frame walls, the parameters of the SDOF model can be defined proportionally to the wall length. This may be used as a simple and easy-to-use tool to compute the dynamic behavior of mid-rise timber buildings with strong wood frame walls.